2007
DOI: 10.1892/06-201.1
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Immunotherapy of Feline Fibrosarcoma with Recombinant Feline Interferon-ω

Abstract: Background: Recombinant feline interferon-v (rFeIFN-v) was tested as a treatment option for cats with fibrosarcoma to assess safety and feasibility.Hypothesis: Treatment with rFeIFN-v in cats with fibrosarcoma is safe and feasible. Animals: Twenty domestic cats. Methods:In an open-labeled uncontrolled clinical trial 12 injections of 1 3 10 6 U/kg rFeIFN-v were administered over a 5-week period: the 1st through 4th injections were given intratumorally, and the 5th through 12th injections were administered subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…In vivo, IFN can affect the differentiation and activity of host immune cells and exert anti‐angiogenic activity (indirect activity) 30 . rFeIFN‐ω was shown to increase the expression of major histocompatibility complex class I molecules on five unrelated feline fibrosarcoma cell lines 15 . Human preclinical studies on the antitumour efficacy of IFN‐ω rely on xenogeneic models of human cancer in immunodeficient mice because of the lack of IFN‐ω genes in mice 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, IFN can affect the differentiation and activity of host immune cells and exert anti‐angiogenic activity (indirect activity) 30 . rFeIFN‐ω was shown to increase the expression of major histocompatibility complex class I molecules on five unrelated feline fibrosarcoma cell lines 15 . Human preclinical studies on the antitumour efficacy of IFN‐ω rely on xenogeneic models of human cancer in immunodeficient mice because of the lack of IFN‐ω genes in mice 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant feline IFN‐ω (rFeIFN‐ω, Virbagen Omega®, Virbac) has been approved for use in cats and dogs against selected infectious diseases 11,12 and has demonstrated in vitro growth inhibition activities on various canine and feline cell lines 13,14 . In a recent clinical study of feline fibrosarcoma, rFeIFN‐ω was shown to be safe and well tolerated for the treatment of this disease but few conclusions could be drawn on its antineoplastic activity because of the lack of clinical controls 15 …”
Section: Introductionmentioning
confidence: 99%
“…Many have investigated the in vitro and/or in vivo effects of the soluble cytokine (eg, interferons, IL-2, IL-12, and IL-15) [38][39][40][41][42][43][44][45][46][47][48][49] or liposome encapsulation of the cytokine (eg, liposomal IL-2) 39,50-53 or use a virus, cell, liposome-DNA complex, plasmid, or other mechanism to expresses the cytokine (eg, recombinant poxvirus expressing IL-2). 50,54-61 The European Committee for Medicinal Products for Veterinary Use adopted a positive opinion in March 2013 for the veterinary product, Oncept IL-2 (feline poxvirus expressing recombinant feline IL-2).…”
Section: Recombinant Cytokines Growth Factors and Hormonesmentioning
confidence: 99%
“…45 Feline interferonomega injected intratumourally and at the tumour excision site has been shown to be safe, 46 but there are no studies regarding its efficacy. Although mainly a spontaneous tumour, OSA has also been described secondary to forelimb fracture 55,56 and radiotherapy.…”
Section: Possible New Treatmentsmentioning
confidence: 99%